Increased expression of human type IIa secretory phospholipase A2 antigen in arthritic synovium. Issue 9 (1st September 1998) - Jamal, Omar S; Conaghan, Philip G; Cunningham, Anne M; Brooks, Peter M; Munro, Vincent F; Scott, Kieran F
Abstract : OBJECTIVE: To determine the localisation and level of expression of human type IIa secretory phospholipase A2 (sPLA2 ) in the synovium of rheumatoid arthritis (RA), osteoarthritis (OA), and non-arthritic (NA) patients and to examine the relation between sPLA2 and histological features of inflammation. METHODS: Immunoperoxidase staining using the anti-sPLA2 monoclonal antibody 9C1 was performed on frozen sections of knee synovium of 10 RA, 10 OA, and 10 NA patients. sPLA2 positive cells were scored on a scale of 0–3 in 10 fields of a representative tissue section from each case. Double labelling imunofluorescence confocal microscopy with antibodies to CD14 or CD45 and 9C1 was used to determine cell type specificity. Inflammation was assessed by semiquantitative scoring of lining layer thickness and mononuclear cell infiltrates (MC) and a cumulative inflammation score, generated by summing the two parameters. Scores in each group were compared using non-parametric statistical analysis. RESULTS: sPLA2 was localised to endothelium (EC), vascular smooth muscle (VSM), and mast cells (M) in all tissue sections. In RA and OA sections, staining was seen in both macrophage-like and fibroblast-like cells in the synovial lining layer (LL) and subsynovial lining layer (SLL). Perineural cells stained positively. Subintimal lymphoid aggregates (LA) were negative in all sections. The RA group showed significantly greater staining in extravascular synovial tissue (median 3.6, range 1.5–6.0) than the OA (median 1.95, range 0–5.3) or NA (median 0, range 0–5.9) groups (p<0.05). LL staining was significantly higher in RA than both OA and NA sections (p<0.05). The OA group showed a trend to higher staining scores than the NA group that did not reach significance. There was a significant correlation between the sPLA2 staining score and inflammation score within the RA patient group (p<0.05). CONCLUSIONS: The synovium is a site of increased expression of sPLA2 antigen in both RA and OA relative to NA. Its presence in both fibroblast and macrophage-like cells in the LL and SLL of synovial tissue in RA and OA, but not NA, indicates that the enzyme is specifically induced in these regions in both conditions with expression in the LL being particularly characteristic of RA. The widespread expression of sPLA2 in synovium suggests it is likely to play a significant part in synovial pathology